Importance of transcript levels of caspase-2 isoforms S and L for breast carcinoma progression. (March 2013) - Brynychová, Veronika; Hlaváč, Viktor; Ehrlichová, Marie; Václavíková, Radka; Pecha, Václav; Trnková, Markéta; Wald, Martin; Mrhalová, Marcela; Kubáčková, Kateřina; Pikus, Tomáš; Kodet, Roman; Kovář, Jan; et al.
Aim: A role of caspase-2 in chemotherapy-induced apoptosis has been suggested. Our study aimed to evaluate the prognostic and predictive importance of caspase-2 isoforms in breast cancer patients.Materials & methods: Caspase-2L and -2S transcript levels were determined in paired tumor and non-malignant control tissues from 64 patients after neoadjuvant chemotherapy and 100 pretreatment patients (general set) by real-time PCR with absolute quantification.Results: Low but statistically significant upregulation of caspase-2L in tumor versus control tissues was observed in both sets. Significant associations of the levels of caspase-2L, -2S or S/L ratio with clinical prognostic factors were observed. However, none of these associations were confirmed in both sets. Levels of caspase-2 isoforms or the S/L ratio did not significantly associate with progression-free survival in the general set or with chemotherapy response in the neoadjuvant set.Conclusion: Our results suggest that the role of caspase-2 isoforms in the progression of breast cancer may considerably differ between pre- and post-chemotherapy patients.